Collective motion in nature - Tan, Hui Luan (2018)
Collective motion refers to the emergence of a global phenomena by natural systems which interact locally. The aim of this report is to understand collective motion by considering the statistical physics behind this collective occurrence. An investigation on the foraging behaviour of an ant colony was carried out using a simplistic Vicsek model that was modified appropriately to fit an ant system. The model would take into account the local interaction rules generally adhered by groups of animals and insects, as well as the effect in which pheromones have on individual ants. Through analysing the order parameter which relates to the orientation of the group as a whole, our simulations showed that ants self-organised into an ordered state forming lanes between the food source and the nest. The ants move either in the same or opposite directions in the pheromone trail. By considering their absolute orientation, they exhibit a collective behaviour where no direct communication is involved. The results generated from the simulations indicated that the ant system could transit fully from a disordered state to an ordered state under a certain range of chosen physical parameters – velocity of ants and noise factor (or the randomness in system). The velocity autocorrelation function as well the two point velocity correlation function further supported the occurrence of phase transition in the ant system during their food raid.